Effects of E-Business Adoption on Organizational Agility in the COVID-19 Context - Espírito Santo, Pedro Manuel (2022)
The COVID-19 pandemic caused a confinement in world society that had no memory of such an event. This event caused the associations to accelerate the online transaction processes, so the continuity of the companies depended on the adoption of e-business systems, which resulted in greater flexibility and agility in the business. Digital transformation and organizational agility are two concepts present in the current COVID-19 context and the adoption of e-business systems depends on the human knowledge existing in the associations. In this context, we developed a study that aimed to study the effects of adopting e-business systems on business agility. For this, we identified that knowledge management is a basis for companies to implement e-business systems. Thus, we carried out an investigation that, through PLS estimation, found that business agility depends on the adoption of e-business systems in a pandemic context such as the case of COVID-19. In this sense, we present theoretical and practical statements of this study.DOI: https://doi.org/10.54663/2182-9306.2022.sn11.45-61